Answer:
C
Step-by-step explanation:
From the table we see that
![f(-2)=12\\ \\f(-1)=10\\ \\f(0)=8\\ \\f(1)=6\\ \\f(2)=4](https://tex.z-dn.net/?f=f%28-2%29%3D12%5C%5C%20%5C%5Cf%28-1%29%3D10%5C%5C%20%5C%5Cf%280%29%3D8%5C%5C%20%5C%5Cf%281%29%3D6%5C%5C%20%5C%5Cf%282%29%3D4)
Thus, the inverse function has the rule
![f^{-1}(12)=-2\\ \\f^{-1}(10)=-1\\ \\f^{-1}(8)=0\\ \\f^{-1}(6)=1\\ \\f^{-1}(4)=2](https://tex.z-dn.net/?f=f%5E%7B-1%7D%2812%29%3D-2%5C%5C%20%5C%5Cf%5E%7B-1%7D%2810%29%3D-1%5C%5C%20%5C%5Cf%5E%7B-1%7D%288%29%3D0%5C%5C%20%5C%5Cf%5E%7B-1%7D%286%29%3D1%5C%5C%20%5C%5Cf%5E%7B-1%7D%284%29%3D2)
This gives us that ordered pairs
![(12,-2),\ (10,-1),\ (8,0),\ (6,1),\ (4,2)](https://tex.z-dn.net/?f=%2812%2C-2%29%2C%5C%20%2810%2C-1%29%2C%5C%20%288%2C0%29%2C%5C%20%286%2C1%29%2C%5C%20%284%2C2%29)
are on the graph of the inverse function
Answer:
267
Step-by-step explanation:
We are given the expression: 6 (d - f) +f
The value of the expression when d= 47 and f = 3 is :
6 (47 - 3) +3 = 6×(44) + 3 = 264 + 3 = 267
=267
Answer:
2x+10
hope this helps
have a good day :)
Step-by-step explanation: